Placebo‐controlled Phase 2 Trial of Drisapersen for Duchenne Muscular Dystrophy. Issue 8 (11th July 2018) - McDonald, Craig M.; Wong, Brenda; Flanigan, Kevin M.; Wilson, Rosamund; de Kimpe, Sjef; Lourbakos, Afrodite; Lin, Zhengning; Campion, Giles; ,
Abstract: Objective: This double‐blind, randomized, placebo‐controlled Phase 2 study (NCT01462292) assessed the 24‐week efficacy, safety, tolerability, and pharmacokinetics of two different subcutaneous drisapersen doses, and the 24‐week off‐dose persistent effect, in ambulant Duchenne muscular dystrophy (DMD) patients. Methods: Male DMD patients (≥5 years; time to rise from floor ≤15 s) were randomized to drisapersen 3 mg/kg/week, 6 mg/kg/week or placebo. The primary efficacy endpoint was change from baseline in 6‐minute walking distance (6MWD) at week 24. Secondary endpoints included changes in timed function tests, muscle strength, and pulmonary function tests. Results: Fifty‐one patients were randomized to placebo ( N = 16), drisapersen 3 mg/kg/week ( N = 17) or 6 mg/kg/week ( N = 18). All but 2 patients had baseline rise from floor time <7 s. This study was exploratory and not prospectively powered; however, a difference in mean 6MWD versus placebo in favor of drisapersen 6 mg/kg/week was observed at week 24 (27.1 m; P = 0.069) and maintained 24 weeks off‐treatment (27.9 m; P = 0.177). The 3 mg/kg/week group showed no statistically significant difference in mean 6MWD versus placebo. For some secondary endpoints, a more positive response in favor of drisapersen 6 mg/kg/week compared to placebo was shown. Drisapersen had a long half‐life with steady state reached after approximately 36 weeks. Most common adverse events in both drisapersen groups were related to injection site reactions and subclinical proteinuria. Interpretation: Drisapersen 6 mg/kg/week for 24 weeks resulted in a treatment benefit in 6MWD, largely maintained 24 weeks off‐treatment. This study provided insights for further studies to optimize dosage regimen.